The endocrinology of 1α-hydroxycorticosterone in elasmobranch fish: A review - Anderson, W. Gary (Comparative biochemistry and physiology. Part A, Molecular & integrative physiology, 2012)
The endocrine underpinnings of the stress response in fish have been the subject of intense research for well over 50years. Much of the research has focussed on teleost fish and so the endocrine mechanisms for cortisol production, transport and action at the target site have received significant attention. However, corticosteroidogenesis in elasmobranchs is exceptional on a number of levels. Unlike teleost fish the interrenal tissue is anatomically distinct from both renal and chromaffin (catecholamine producing) tissue; further the final product, 1α-hydroxycorticosterone (1α-OH-B), is unique to chondrichthyans where the carbon atom at position 1 of corticosterone has a hydroxyl group attached in the α orientation. The homologous nature of interrenal tissue in elasmobranchs presents an obvious advantage in the study of corticosteroidogenesis, however, the unique chemical nature of 1α-OH-B has presented distinct disadvantages as it has proven to be difficult to synthesise, and therefore studies examining the mineralocorticoid and glucocorticoid actions of this steroid are limited. Over the last decade molecular techniques have provided significant insight in the involvement of corticosteroiogenic enzymes in the elasmobranch interrenal in addition to the evolution of corticosteroid receptors. Given the number of excellent reviews focussing on the role of cortisol in the stress response of teleost fish, this short review aims to synthesise the endocrine basis for the synthesis, release, and action, of the enigmatic 1α-OH-B in elasmobranch fish.